Factors that influence the adoption of fintech by small and medium enterprises in South Africa - Martino, Sibongile (University of the Witwatersrand, Johannesburg, 2023)
Adoption of a payment system is considered a steppingstone toward full digital economy participation and has made it simpler for small and medium-sized (SMEs) businesses to acquire financial products and services. However, payment system success strongly relies on merchant involvement, which provides customers with a valued service and contributes to improved customer experience, data collection, and financial performance. The POS market in South Africa is the largest in Africa, however adoption is slowest among SMEs. This research employs the TOE framework to investigate whether the technological, organisational, and environmental contexts of SMEs in Gauteng, South Africa impact their adoption of POS systems. Twenty Gauteng-based SMEs were interviewed for this study to address the research question. This objective was achieved by deconstructing the study findings about the primary and secondary components of the TOE framework. In addition, the interpretivist approach used in this study's analysis of the semi- structured interviews shed light on the factors that influence the adoption of POS by SMEs. This study found that the decision of SME owner-managers to adopt a POS system is influenced by motivating and inhibiting factors that stem from the technological, organisational, and environmental context in which a SME operates. The study also found that the availability of technology, its value proposition, and an enabling organisational structure motivated the adoption of POS systems by SMEs. Nonetheless, the research found that cost, a burdensome regulatory environment, and a lack of infrastructural support, such as lack of a reliable power system, are obstacles to the broad adoption of POS systems.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Fintech; Point-of-Sale; Merchant adoption Small and Medium- Sized Enterprises (SME); Technological-Organisational- Environmental (TOE) framework; South Africa; UCTD; SDG-8: Decent work and economic growth